1997
DOI: 10.1039/a702845h
|View full text |Cite
|
Sign up to set email alerts
|

Large variation of rates for platination of phosphorothioate-containing oligonucleotides: end effects and counter ion influence

Abstract: † [HC 8 H 4 O 4 2 ] = 0.50 mm, pH = 4.2 adjusted with HClO 4 . ‡ Available upon request from the authors. § Obtained as k obs /[Pt II ] tot .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…These results suggest that preassociation of metal complex with negatively charged oligonucleotide backbone contributes formation of coordination bond. Similar influence of electrostatic interactions on kinetics has been reported previously for a reaction of platinum complexes with various types of oligonucleotides [22,23].…”
Section: Hplc Monitoring Of the Reaction Kineticssupporting
confidence: 61%
“…These results suggest that preassociation of metal complex with negatively charged oligonucleotide backbone contributes formation of coordination bond. Similar influence of electrostatic interactions on kinetics has been reported previously for a reaction of platinum complexes with various types of oligonucleotides [22,23].…”
Section: Hplc Monitoring Of the Reaction Kineticssupporting
confidence: 61%
“…See DOI: 10.1039/b719542g oligo-and polymers. 12 In a recent study published by us, we were able to show that the rate enhancement obtained in oligomeric systems reaches a maximum around an oligomer length of ca. 20 bases.…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies by us have shown that the kinetics for adduct formation reactions with donor groups located on the charged phosphodiester backbone are sensitive towards factors such as (1) the size of the reacting DNA oligomer [7,14], (2) the exact location of the binding site [15,16] and (3) the choice and concentration of counterions used in the supporting electrolyte [7,15,16]. The kinetics data could be fitted to a reaction model in which pre-association of the platinum complex precedes the adduct formation reaction.…”
Section: Introductionmentioning
confidence: 99%